Research on the Impact of Online Marketing on Enterprise Performance: Analysis of Financial Statements Based on the Food Industry - Liu, Qiuping; Jiang, Li; Jin, Jing (International Journal of Global Economics and Management, 2023)
With the development of network economy and e-commerce technology, the expansion of online marketing models for enterprises has become an inevitable trend. Online marketing has broken through the time and space limitations of merchants selling products. Enterprises use multimedia technology to interact with customers online, display products, and increase market sales. This article takes Uni President Enterprise as an example and uses case analysis method to analyze the financial performance of relevant financial indicators of Uni President Enterprise. Based on market conditions, it adjusts online marketing strategies, expands the brand awareness of the enterprise, enhances sales revenue, and improves financial performance, which has a positive effect.